Building analytical platform with Big Data solutions for log files of PanDA infrastructure; Journal of Physics: Conference Series; Vol. 1015 : Information Technologies in Business and Industry (ITBI2018) - Alekseev A. A. Aleksandr Aleksandrovich; Barreiro Megino F. G.; Klimentov A. A.; Korchuganova T. A.; Maendo T.; Padolski S. V. (Mathematical simulation and data processing, 2018)
Title screen